Decision-making and goal-setting in chronic disease management: Baseline findings of a randomized controlled trial() - Kangovi, Shreya (Patient Educ Couns, 2016)
OBJECTIVE: Growing interest in collaborative goal-setting has raised questions. First, are patients making the ‘right choices’ from a biomedical perspective? Second, are patients and providers setting goals of appropriate difficulty? Finally, what types of support will patients need to accomplish their goals? We analyzed goals and action plans from a trial of collaborative goal-setting among 302 residents of a high-poverty urban region who had multiple chronic conditions. METHODS: Patients used a low-literacy aid to prioritize one of their chronic conditions and then set a goal for that condition with their primary care provider. Patients created patient-driven action plans for reaching these goals. RESULTS: Patients chose to focus on conditions that were in poor control and set ambitious chronic disease management goals. The mean goal weight loss −16.8lbs (SD 19.5), goal HbA1C reduction was −1.3% (SD 1.7%) and goal blood pressure reduction was −9.8 mmHg (SD 19.2 mmHg). Patient-driven action plans spanned domains including health behavior (58.9%) and psychosocial (23.5%). CONCLUSIONS: High-risk, low-SES patients identified high priority conditions, set ambitious goals and generate individualized action plans for chronic disease management. PRACTICE IMPLICATIONS: Practices may require flexible personnel who can support patients using a blend of coaching, social support and navigation.